Technology Adaptation in Japan’s Work Culture: Usage of Electronic Signatures (E-Signatures) in Post-COVID-19 Japan - Diva Gabriela Prawiro; Fourmando Butar Butar; Jimmy Gotomo; Elisa Carolina Marion (Engineering Proceedings)
Hanko or signature seals are widely used by Japanese companies to sign business contracts. However, the COVID-19 pandemic has caused Hanko culture in Japan to become ineffective, especially in teleworking. The pandemic has also negatively affected the global economy, including Japan. To face this issue, the Japanese government has expanded the use of electronic signatures since 2020. Regardless of the government’s efforts, many Japanese companies have not implemented the use of electronic signatures. Nevertheless, the prospects of utilizing electronic signatures in Japanese companies have increased due to post-COVID-19 socio-economic factors. We examined the problem of Hanko culture and how Hanko is replaced by electronic signatures in Japan’s society through an inductive, descriptive, and qualitative method. By using those approaches, we discovered that, in the short run, Japanese companies will be forced to adapt to the use of electronic signatures to increase productivity post-economic crisis. In the long run, Japanese companies will be inclined to use electronic signatures to adapt to global trade conditions.